EFFECT OF FICUS DELTOIDEA JACK. TO NEUTROPHIL AND MACROPHAGE CELLS IN ORAL WOUND HEALING - Maharani Laillyza Apriasari; I Wayan Arya Krishnawan Firdaus; Rahayu Wida Sari Fitri; Hana Nur Ishmah; Selviana Rizky Pramitha; Nurul Inaas Mahamad Apandi (Dentino: Jurnal Kedokteran Gigi, 2026)
Background: Oral mucosal wounds require effective inflammatory control for optimal healing. However, conventional agents such as povidone-iodine may cause irritation and cytotoxicity, limiting their use. Ficus deltoidea, a medicinal plant from Kalimantan, possesses antimicrobial, antioxidant, and anti-inflammatory properties, making it a promising alternative for oral wound therapy. Objectives: To evaluate the effect of Ficus deltoidea leaf extract gel on neutrophil and macrophage cells in oral mucosal wound healing. Methods: A true experimental posttest-only control group study was conducted on 48 male Wistar rats. Standardized buccal mucosal wounds were treated with Ficus deltoidea J. leaf extract gel (GEDTB) 5%, 10%, 15% or gel base (control). Animals were sacrificed on days 1, 3, and 7, and neutrophil and macrophage counts were assessed histopathologically. Data were analyzed using two-way ANOVA with Bonferroni post hoc. Results: Neutrophil counts decreased significantly over time in all groups, with a faster reduction in extract-treated groups, particularly at 15%. On day 1, the control group had the highest neutrophil count, significantly greater than the 15% group (p<0.05), while by day 7, all treatment groups showed significantly lower neutrophil levels than control. Macrophage counts increased from day 1, peaked on day 3—highest in the 15% group—and declined significantly by day 7. Both treatment and time had significant effects on neutrophil and macrophage counts (p<0.05), with a significant interaction observed for macrophages. Conclusion: Ficus deltoidea J. leaf extract gel effectively modulates inflammatory cell by accelerating neutrophil reduction and enhancing macrophage activity in oral wound healing.Keywords: Anti-inflammatory activity, Ficus deltoidea jack.,Macrophages, Neutrophils, Oral wound healing